O-GlcNAc regulates the mitochondrial integrated stress response by regulating ATF4 - Alghusen, Ibtihal M.; Carman, Marisa S.; Wilkins, Heather; Ephrame, Sophiya John; Qiang, Amy; Dias, Wagner B.; Fedosyuk, Halyna; Denson, Aspin R.; Swerdlow, Russell H.; Slawson, Chad (Frontiers in Aging Neuroscience, 2023)
Background Accumulation of mitochondrial dysfunctional is a hallmark of age-related neurodegeneration including Alzheimer’s disease (AD). Impairment of mitochondrial quality control mechanisms leading to the accumulation of damaged mitochondria and increasing neuronal stress. Therefore, investigating the basic mechanisms of how mitochondrial homeostasis is regulated is essential. Herein, we investigate the role of O-GlcNAcylation, a single sugar post-translational modification, in controlling mitochondrial stress-induced transcription factor Activating Transcription Factor 4 (ATF4). Mitochondrial dysfunction triggers the integrated stress response (ISRmt), in which the phosphorylation of eukaryotic translation initiation factor 2α results in the translation of ATF4. Methods We used patient-derived induced pluripotent stem cells, a transgenic mouse model of AD, SH-SY5Y neuroblastoma and HeLa cell-lines to examine the effect of sustained O-GlcNAcase inhibition by Thiamet-G (TMG) on ISRmt using biochemical analyses. Results We show that TMG elevates ATF4 protein levels upon mitochondrial stress in SH-SY5Y neuroblastoma and HeLa cell-lines. An indirect downstream target of ATF4 mitochondrial chaperone glucose-regulated protein 75 (GRP75) is significantly elevated. Interestingly, knock-down of O-GlcNAc transferase (OGT), the enzyme that adds O-GlcNAc, in SH-SY5Y increases ATF4 protein and mRNA expression. Additionally, ATF4 target gene Activating Transcription Factor 5 (ATF5) is significantly elevated at both the protein and mRNA level. Brains isolated from TMG treated mice show elevated levels of ATF4 and GRP75. Importantly, ATF4 occupancy increases at the ATF5 promoter site in brains isolated from TMG treated mice suggesting that O-GlcNAc is regulating ATF4 targeted gene expression. Interestingly, ATF4 and GRP75 are not induced in TMG treated familial Alzheimer’s Disease mice model. The same results are seen in a human in vitro model of AD. Conclusion Together, these results indicate that in healthy conditions, O-GlcNAc regulates the ISRmt through regulating ATF4, while manipulating O-GlcNAc in AD has no effect on ISRmt.